Villagers’ Perception and Attitude Toward Wetland Values and Conservation in Vietnam: A Case Study of Xuan Thuy Ramsar National Park - Truong, Dinh Duc (Frontiers in Sociology, 2021)
Perception and attitude toward wetland values and conservation are essential to the sustainable management and wise use of this resource. This study examined the attitudes of local communities towards the values and management of Xuan Thuy National Park (XTNP) in Vietnam. The study also explores factors affecting conservation attitudes in the study area. A survey was implemented to 677 households randomly selected in five communes adjacent to XTNP. In addition, focus group discussions, and interviews with selected key informants were conducted. The study shows that local villagers generally hold positive attitudes towards wetland conservation. However, awareness of the threats to wetlands and the national park rules are not high. People are willing to sacrifice part of their income to preserve wetlands for future generations. Age, length of residency, and schooling year are observed to be significantly impacting attitudes towards wetland conservation. It is critical to connect management agencies and people to propagate conservation regulations and XTNP zoning for sustainable wetland management and conservation. Social networks and the internet are potential vehicles for increasing understanding and connection.